Vanishing Valentines - Auerbach, Annie; Godfree, Ghia; Roe, David (Los Angeles Disney Press, 2024)
When Valentine's Day cards and treats go missing throughout Kittydale, the SuperKitties must track down the thief to save the holiday. This pawsome foursome of adorable kitties transform into fierce, furry super heroes anytime justice needs to be served. Based on the hit Disney Junior series SuperKitties, this early reader is perfect for fans aged 4 to 6.
115478
Keywords: Cats -- Juvenile fiction; Superheroes -- Juvenile fiction; Valentines -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Lost articles -- Juvenile fiction; Readers (Elementary); Animal fiction; Picture books